Attitude control: A key factor during the design of low-thrust propulsion for CubeSats. (November 2020) - Quinsac, Gary; Segret, Boris; Koppel, Christophe; Mosser, Benoît
Abstract: Orbital capability is a decisive step forward for nanosatellites in general and CubeSats in particular. Although trajectory maneuvers and their implementation have been thoroughly studied for classical satellites, the high level of constraints on CubeSats in terms of mass, volume and power, makes the transition delicate. Orbit, attitude and power control subsystems available for this format limit too optimistic performance available in literature. To verify this hypothesis, we simulate trajectory maneuvers in Earth orbit with representative CubeSat hardware and software. A low-thrust trajectory solver based on classical orbital elements from the literature is adapted to our context. A home-made attitude control simulation tool is coupled to include both control and perturbative dynamics. Increases in time and propellant consumption of more than 100% are caused by thrust direction errors such as misalignments and attitude control limitations, sometimes leading to mission loss. These results highlight an important increase in complexity for the CubeSat format that is not covered by the usual approach. Such limitations should be considered from the very start of the design of a nanosatellite mission with trajectory modification requirements. Highlights: Usual approach considers GNC and ADCS independently on CubeSats. Thrust disturbance torques are unavoidable and saturate reaction wheels (RW). RW desaturation either extend maneuver duration or increase propellant consumption. Mutual impacts between GNC and ADCS can lead to CubeSat loss. Design of CubeSat with propulsion must focus on ADCS before trajectory optimization.